2021
DOI: 10.1128/aac.02141-20
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Acute Kidney Injury Potential with the Combination of Vancomycin and Imipenem-Cilastatin/Relebactam or Piperacillin/Tazobactam in a Preclinical Model

Abstract: Background: This risk of vancomycin (VAN)-associated acute kidney injury (AKI) may be altered with combination regimens. The specific AKI risk when VAN is combined with imipenem-cilastatin/relebactam (IMP-C/REL) or piperacillin/tazobactam (TZP) has not been clearly defined. Objectives: To quantify the dose-AKI relationships of VAN alone and in combination with TZP or imipenem-cilastatin/relebactam (IMP-C/REL). Methods: Ten to twelve week old male C57BL/6J mice (Charles River Laboratory) were dosed with study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
7
11
0
Order By: Relevance
“…Our findings of isolated increases in creatinine that were not matched by changes in either Cys-C or BUN are consistent with this hypothesized mechanism. Our findings are also consistent with animal studies suggesting that PT does not enhance VN toxicity [6,[8][9][10], with some suggesting that PT may actually reduce VN nephrotoxicity. A caveat to the animal models is that, beyond demonstrating no adverse effect on kidney function, some have also shown that VN + PT does not increase creatinine concentrations [8,9].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings of isolated increases in creatinine that were not matched by changes in either Cys-C or BUN are consistent with this hypothesized mechanism. Our findings are also consistent with animal studies suggesting that PT does not enhance VN toxicity [6,[8][9][10], with some suggesting that PT may actually reduce VN nephrotoxicity. A caveat to the animal models is that, beyond demonstrating no adverse effect on kidney function, some have also shown that VN + PT does not increase creatinine concentrations [8,9].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are also consistent with animal studies suggesting that PT does not enhance VN toxicity [ 6 , 8 – 10 ], with some suggesting that PT may actually reduce VN nephrotoxicity. A caveat to the animal models is that, beyond demonstrating no adverse effect on kidney function, some have also shown that VN + PT does not increase creatinine concentrations [ 8 , 9 ]. Nevertheless, regardless of mechanism, the data raise doubt that PT enhances VN-mediated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even less is known about agents that can prevent kidney injury due to vancomycin. Imipenem-cilastatin/relebactam has been shown to decrease serum creatinine of mice that received vancomycin (He, Souza, Matvekas, Crass, & Pai, 2021) with similar findings reported in retrospective clinical studies (Hakeam, AlAnazi, Mansour, AlFudail, & AlMarzouq, 2019).…”
Section: Introductionsupporting
confidence: 70%
“…kidney injury molecule-1 [KIM-1], clusterin, and osteopontin (OPN)) and histopathology (15). In these models, results conflicted with retrospective human studies; additive nephrotoxicity associated with VAN+TZP was not observed in animal studies (15,16). KIM-1 was identified as the most relevant urinary biomarker in animal studies for vancomycin induced kidney injury, correlating with GFR changes and end-organ histopathologic damage at proximal tubule (15,(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%